Dynamical mass loss from unstable giants - Clayton, M (2018)
Giant stars are believed to lose significant fractions of their total mass over their lifetimes, but the mechanisms responsible for this are ill-understood. One possible mechanism is dynamical mass loss – a hydrodynamical process in which matter is ejected from the stellar surface in ballistic outflows. In this thesis, dynamical mass loss is studied in three stellar regimes: common-envelope objects, asymptotic giant branch stars, and red supergiants. Using hydrodynamical simulations performed with the stellar evolution code MESA, we examine the dynamical behaviour and stability of stars in each of these regimes. We examine the dynamical properties of common-envelope objects during the slow spiral-in phase using a parameterised 1-dimensional model of orbital dissipatory heating. We find that the envelope becomes unstable to high-amplitude dynamical pulsations that can lead to repeated mass-ejection events capable of removing the entire envelope and terminating the common-envelope phase. We estimate this process's α efficiency value and suggest how these results might be employed in parameterised common-envelope models. We employ coupled evolutionary and hydrodynamical simulations of AGB stars to study their dynamical properties as they traverse the TP-AGB and examine their dependence on basic stellar properties and on the thermal pulse cycle. We find that these models experience large amounts of dynamical mass loss, and we construct a parameterised model to estimate its strength. We find that this model is successful at locating the termination of the AGB. We apply a similar approach to a study of RSGs, and find that dynamical mass loss also emerges in this regime. We estimate the conditions under which this occurs and discuss how this mechanism may resolve theoretical problems relating to the Humphreys-Davidson limit and the progenitors of SNe IIn. We conclude that dynamical mass loss is likely to form a vital part of the mass-loss histories of cool giant stars.